2013
DOI: 10.5430/ijfr.v4n3p10
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management Prior to Initial Public Offerings and Its Effect on Firm Performance: International Evidence

Abstract: This paper investigates the degree of discretionary current accruals (DCA -1 ) prior to the initial public offerings (IPOs) of foreign firms in an attempt to study the two seemingly opposing views of Teoh, Welch, and Wong (1998) and Ball and Shivakumar (2008) in regards to pre-IPO earnings management. By analyzing a sample of 4962 IPOs from 28 countries, I find that, on average, IPO firms do not report significantly positive DCA -1 . This result supports the view held by Ball and Shivakumar that IPO firms do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
2
Order By: Relevance
“…While a number of studies have documented that IPO firms engaged in aggressive earnings management during a pre-IPO period in order to inflate income, other studies do not support this finding. Different views are provided by researchers such as Armstrong et al (2008), Ball and Shivakumar (2008), Chou et al (2009), Fan (2007), Premti (2013), and Alsultan (2017) who found that firms did not engage in earnings management in the year before the IPO or the year of going public. Similarly, in the context of SEO, a high level of information asymmetry in the SEO event provides an opportunity for managers to manipulate earnings upward to maximize offering proceeds.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…While a number of studies have documented that IPO firms engaged in aggressive earnings management during a pre-IPO period in order to inflate income, other studies do not support this finding. Different views are provided by researchers such as Armstrong et al (2008), Ball and Shivakumar (2008), Chou et al (2009), Fan (2007), Premti (2013), and Alsultan (2017) who found that firms did not engage in earnings management in the year before the IPO or the year of going public. Similarly, in the context of SEO, a high level of information asymmetry in the SEO event provides an opportunity for managers to manipulate earnings upward to maximize offering proceeds.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Penelitian sebelumnya telah dilakukan untuk mengetahui apakah terjadi manajemen laba di sekitar periode IPO dan menemukan bahwa tidak adanya manajemen laba yang signifikan sebelum periode IPO dan manajemen cenderung konservatif dalam menyajikan laporan keuangan pada prospektus. (Ball & Shivakumar, 2008), (Premti, 2013), (Teoh et al, 1998) dan (Widyaningtyas, 2009). Penelitian terdahulu juga menunjukkan bahwa manajemen laba lebih signifikan dilakukan pada periode IPO karena manajemen memiliki insentif untuk mempertahankan harga saham selama lock-up period dan untuk menghindari risiko litigasi jika terjadi penurunan laba dan harga saham yang signifikan pada periode IPO (Alhadab et al, 2015), (Premti, 2013), dan (Teoh et al, 1998).…”
Section: Pendahuluanunclassified
“…Tidak ditemukan manajemen laba akrual pada periode sebelum IPO yang signifikan yang bertujuan untuk meningkatkan laba seperti pandangan pada umumnya. Premti (2013) melakukan penelitian terhadap manajemen laba sebelum periode IPO dan pada periode IPO terhadap 4962 sampel perusahaan yang berasal dari 28 negara yang berbeda. Penelitian ini hanya mengukur manajemen laba menggunakan discretionary accrual saja.…”
Section: Pendahuluanunclassified
“…One view provides strong empirical evidence that some firms manipulate accruals aggressively or earnings upward around new issuance (Ahmad-Zaluki, 2008;Chiraz, 2013;DuCharme et al, 2004;Gresse & Gajewski, 2006;Li et al, 2005;Mangala & Dhanda, 2019;Nuryaman, 2013;Roosenboom et al, 2003;Teoh et al, 1998aTeoh et al, , 1998b. Different views are provided by researchers such as Beaver et al (2000), Qintao (2007), Ball and Shivakumar (2008), Armstrong et al (2008), Premti (2013), and Chou et al (2009) which show no evidence of earnings signals around new issuance.…”
Section: Earnings Management Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Several international studies have documented the existence of earnings management surrounding new issuance. Results of these studies illustrate the contrast among levels of accruals earnings management ranging from very aggressive (such as Aharony et al, 1993;DuCharme et al, 2004;Friedlan, 1994;Kao et al, 2009;Nuryaman, 2013;Rangan, 1998;Shivakumar, 2000;Teoh et al, 1998aTeoh et al, , 1998b to no earnings management (such as Armstrong et al, 2008;Ball & Shivakumar, 2008;DuCharme et al, 2001;Premti, 2013) to no earnings management (such as DuCharme et al, 2001;Ball & Shivakumar, 2008;Armstrong et al, 2008;Premti, 2013). Review of the earnings management around issuance of equity and new listings indicates that while earnings management during issuance of equity is fully documented, the study on accruals earnings management and new listings is not strong enough.…”
Section: Introductionmentioning
confidence: 99%